Cytotoxic phloroglucinol meroterpenoid from Eugenia umbelliflora fruits. (October 2018) - Farias, Ingrid V.; Faqueti, Larissa G.; Noldin, Vania Floriani; Franchi Junior, Gilberto; Nowil, Alexandre E.; Schuquel, Ivania T.A.; Delle Monache, Franco; García, Pablo A.; López-Pérez, José L.; San Feliciano, Arturo; Cechinel-Filho, Valdir; Meyre-Silva, Christiane
Graphical abstract: Highlights: We isolated five phloroglucinol derivatives. The extracts showed good cytotoxicity; eugenials C, eugenial D and eugenial E showed activity against K562 and B16F10 cells. Structure elucidation of a sesquiterpenyl phloroglucinol (eugenial E) Eugenial E (5) described here for the first time. Abstract: Eugenia umbelliflora is a member of Myrtaceae family, with antimicrobial and anti-leishmanial properties related to the presence of phloroglucinol derivatives in its extracts. This study describe the isolation and structure elucidation of a sesquiterpenyl phloroglucinol (eugenial E), that is described here for the first time. Eugenial E (5 ) was isolated from the n -hexane extract of fruits, and its structural elucidation was carried out through the combined analysis of MS, IR and 1D-(¹H, ¹³C BB and DEPT, and NOEDIFF) and 2D-(COSY, HSQC, HMBC and ROESY) NMR spectra, with conformational analysis support. Cytotoxicity was assessed using MTT analysis against human leukemic cells (k562 and Nalm-6 cells) and murine melanoma cells (B16F10 cell). The extracts showed high cytotoxicity, while eugenial C with 0.38 μM, eugenial D 1.9 μM and eugenial E 4.97 μM of IC50 for K562 and for B16F10 cells 6.0; 3.2 and 8.8 μM, respectively. The eugenials were evaluated in silico for prediction of bioactivity, toxicity and molecular properties using the ChemDoodle, Molinspiration and PreADMET services. The results of in silico analysis have shown that eugenial C and eugenial D may be mutagenic. In rats eugenial C, eugenial D and eugenial E may be carcinogenic, and eugenial D may have low-to-medium risk of environmental / developmental toxicity.